Effects of growth substrate on the nucleation of monolayer MoTe2. Issue 45 (13th April 2021) - Hynek, David J.; Singhania, Raivat M.; Hart, James L.; Davis, Benjamin; Wang, Mengjing; Strandwitz, Nicholas C.; Cha, Judy J.
Abstract : Choice of growth substrate is shown to have a significant effect on the conversion of ALD grown molybdenum oxide to monolayer 2H molybdenum ditelluride. Abstract : The discovery and characterization of two-dimensional (2D) materials beyond graphene has increased dramatically over the past decade with increasingly fine control over the growth dynamics of these materials. MoTe2 represents a model material for studying phase change properties of 2D materials due to small energy differences between its 2H semiconducting phase and 1T′ semimetallic phase. Although some substrates are demonstrated to be better than others for the wafer-scale growth of high quality MoTe2 films, substrate effects on the nucleation and growth of MoTe2 are still not well understood. Here, we grow monolayer MoTe2 by converting MoO x thin films deposited on three different substrates: sapphire Al2 O3 (0001), amorphous SiO2, and amorphous AlO x, and examine the early stages of the conversion reaction to elucidate the substrate effects on the nucleation of MoTe2 . We observe that the chemical composition of the substrate is more important than the surface topography and crystallinity of the substrate, with high quality monolayer 2H MoTe2 formed on both Al2 O3 (0001) and AlO x in contrast to mixed phase 2H/1T′ MoTe2 formed on SiO2, as determined by Raman spectroscopy, X-ray photoelectron spectroscopy, and atomic force microscopy.